Towards carbon neutrality in higher education institutions : case of two private universities in Colombia - Ana M. Osorio and Luisa F. Úsuga and Rafael E. Vásquez and César Nieto-Londoño and Maria E. Rinaudo and José A. Martínez and Walter Leal Filho (Sustainability, 2022)
This paper addresses the path followed by two private higher education institutions (HEI) in Colombia towards achieving carbon neutrality. The methodology followed by these universities to achieve a carbon-neutral certification, based on the Greenhouse Gas (GHG) Protocol, is first described. The process of developing the GHG inventory, projected towards the carbon neutrality of these organisations while using the standard ISO 14064:2006, involved a series of steps that were consolidated in three phases: (i) definition of the scope, collection of data and emissions quantification; (ii) analysis of results and mitigation actions; and (iii) verification and compensation strategies. Results for the HEIs are shown in terms of the organisational context, carbon footprint measurement, reduction, verification, and compensation. The case is presented for Universidad Pontificia Bolivariana, a multi-campus university that became the first carbon-neutral university in Latin America in 2017, and Universidad Ean, a single-campus university that became the second carbon-neutral university in Colombia in 2021, as verified by the Colombian Institute of Technical Standards and Certification (ICONTEC). This work shows that universities can play a key role in regional and global agendas with their contribution through the incorporation of sustainability strategies, since HEIs can not only achieve carbon neutrality, but they can help other organisations by delivering graduates who are aware of sustainability and provide specific training towards building a sustainability culture, which is needed for regenerative development.
Keywords: Carbon footprint; Carbon neutrality; Higher education institutions; Regenerative development; Sustainability; Sustainable development